Development of a stabilized natural fiber-reinforced earth composite for construction applications using 3D printing - Silva G. (2019)
The application of additive manufacturing technologies to the construction industry has a wide range of advantages from the economic, social and design flexibility point of view. However, most of up to date research studies have been performed using ordinary Portland cement (OPC)-based mortars and concretes. Therefore, the objective of this article is to explore the development of an eco-friendly earth composite reinforced with natural sisal fibers and chemically stabilized with a hydraulic binder. Analysis of the workability by shear vane tests was performed on fresh earth samples to find the optimum water content in sisal fiber-reinforced earth stabilized with OPC. Afterward, the effect of the addition of OPC on the hardening process was evaluated through shear vane and Vicat needle tests from 0 to 180 min after mixing. The results indicate that water content, fiber addition and OPC replacement have a strong influence on the shear yield strength. Furthermore, the presence of chemical stabilizers as OPC accelerates the hardening process allowing a faster layer-by-layer deposition. This low cost and eco-friendly preliminary earth-based composite can be used for 3D printing applications in the construction industry. © Published under licence by IOP Publishing Ltd.